Program Parenting Skill Berbasis Konseling Sebagai Upaya Meningkatkan Kecerdasan Intrapersonal Dalam Mewujudkan Lingkungan Belajar Ramah Anak - Mahardika, Bagus (Institut Agama Islam Negeri Madura, 2024)
Nowadays, the phenomenon of immoral students is starting to emerge. Cases of students who carry out bullying which leads to fights are a terrible scourge that has not been solved. Considering that children are an investment in the nation, parents really need special programs that can provide education in educating children. The aim of this research is to determine the counseling-based Parenting Skills program in an effort to increase intrapersonal intelligence in children towards a child-friendly learning environment. The research method used in this research is literature study, how the data sources for this research were obtained from books and scientific journals, data collection techniques using documentation techniques on books, journal articles that are relevant to the discussion, data analysis using content analysis, how the data Data in the form of information sources will be processed according to the needs used in studying the phenomenon under study. The research results show that the Parenting Skills program can improve children's intrapersonal intelligence through preventive services, responsive services and developmental services. This counseling approach is able to have a significant impact on children's sensitivity and skills in managing emotions, so that children can adapt and be useful in life in society.